Analysis Of Service Quality And Location Towards Customer Satisfaction At J&T Express Ed Saqila Medan - Annisa Eka Maghfiroh; Rifky Budi Setiawan; Muhammad Dharma Tuah Putra Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The degree of customer happiness is impacted by the location and quality of the service. Consumers will always remember favorable memories, and they are more likely to suggest the experience to others. The goal of this research is to further explore and comprehend the Analysis of Service Quality and Location on Customer Satisfaction at J&T Express ED Saqila Medan. The study's sample size was 100 people. Quantitative approaches were used in this study. The data analysis method employed in this study was purposive sampling, and the results were analyzed using a statistical formula, specifically multiple linear regression analysis with the help of the SPSS version 26 program. According to the results of this research, customer satisfaction is significantly and positively impacted by service quality. Similarly, the site also has a substantial and beneficial impact on how happy clients are. With a percentage of 51. 8%, it may be deduced that there is a strong correlation between service quality and location with customer satisfaction, and that the remaining 48. 2% may be attributed to other variables not covered in this research.